2017
DOI: 10.33588/rn.6505.2017072
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de la ortesis dinámica del miembro superior en la fase crónica del ictus. Estudio longitudinal

Abstract: Objetivo. El ictus es la condición médica más importante que origina discapacidad permanente en el adulto. El objetivo es valorar la eficacia de ortesis dinámicas en la rehabilitación del miembro superior en pacientes que han presentado un ictus. Pacientes y métodos.Estudio longitudinal de casos y controles. Se incluyó una muestra de pacientes procedentes de centros de rehabilitación que presentaban hemiparesia secundaria a ictus isquémico o hemorrágico. De forma aleatoria, los pacientes fueron distribuidos en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…In another study of 16 patients with hemiparesis resulting from brain damage, the use of these devices showed a reduction in muscle tone and swelling, and improved wrist and finger movement [ 51 ]. Although some studies have shown that the use of these devices in people with brain damage improve strength, manual dexterity, and UL functionality, there is a need for studies with larger sample sizes [ 27 , 28 ]. These results coincide with those observed in the present study, in the sense that the implementation of the orthosis showed improvements on motor aspects of UL such as resting tremor, rhythm of hand movements or speed of rapid alternating movements, assessed with Kinesia, leading to an improvement in manual dexterity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study of 16 patients with hemiparesis resulting from brain damage, the use of these devices showed a reduction in muscle tone and swelling, and improved wrist and finger movement [ 51 ]. Although some studies have shown that the use of these devices in people with brain damage improve strength, manual dexterity, and UL functionality, there is a need for studies with larger sample sizes [ 27 , 28 ]. These results coincide with those observed in the present study, in the sense that the implementation of the orthosis showed improvements on motor aspects of UL such as resting tremor, rhythm of hand movements or speed of rapid alternating movements, assessed with Kinesia, leading to an improvement in manual dexterity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, wearing these devices on the foot and ankle improved balance and walking speed in multiple sclerosis [ 25 , 26 ], and pain and function in patients suffering with complex regional pain syndrome (CRPS) [ 16 ]. Stroke has been the condition in which the use of this UL orthosis has been most investigated, and several studies have shown positive effects on strength, manual dexterity, and UL functionality, which need to be confirmed in studies with larger sample sizes [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…En otro estudio de 16 pacientes con hemiparesia resultante de daño cerebral, el uso de estos dispositivos mostró una reducción en el tono muscular y la hinchazón, y mejoró el movimiento de la muñeca y los dedos (109). En el estudio de González et al, realizado con 40 pacientes con daño cerebral, se mostró que la implementación del DEFO en el MS afectado, durante un periodo de 6 meses, producía una mejora en el tono y fuerza muscular, permitiendo mejora funcional (163). Aunque algunos estudios han demostrado que el uso de estos dispositivos en personas con daño cerebral mejora la fuerza, la destreza manual y la funcionalidad del MS, se necesitan estudios con tamaños de muestra más grandes (112).…”
Section: Tabla 11unclassified